Age, source, and regional stratigraphy of the Roraima Supergroup and Roraima-like outliers in northern South America based on U-Pb geochronology - Santos, J.; Potter, P.; Reis, N.; Hartmann, L.; Fletcher, Ian; McNaughton, Neal (Geological Society of America, 2003)
New 207Pb/206Pb ion-microprobe dates from the basement underlying the Roraima Supergroup, from sandstones and tuffs within the supergroup, and from associated mafic intrusions establish new temporal framework for this major stratigraphic unit in northern South America. Zircons from the tuffs within the supergroup yield a Paleoproterozoic age of 1873 6 3 Ma, Orosirian. The minimum age of the Roraima Supergroup was determined by U-Pb geochronology using baddeleyite and zircon from two mafic sills (Avanavero magmatism) and is 1782 6 3 Ma. Zircons of some Roraima-like outliers indicate that they are post-Roraima in age and do not belong to the supergroup. This conclusion is supported by the unconformity between the Mataui and Uaimapue Formations present in the Pacaraima Plateau, which may represent a hiatus as long as 320 m.y. Thus, all the sandstones above the unconformity such as the Mataui Formation, as well as outliers such as the Serra Surucucus, Araca, and Neblina units, do not belong to the supergroup. Rocks of the Roraima Supergroup and post-Roraima sandstones were deposited in two separate but overlapping basins, each 1,200,000 km2 in area. The Roraima Supergroup represents fill in a foreland basin that was derived mostly from the Trans-Amazon orogenic belt to the north and northeast, whereas the fill in the post-Roraima Neblina successor foreland basin was derived from both the Trans-Amazon and Tapajos-Parima orogenic belts to the east and north east. Although most of both basins are largely flat lying or gently deformed, some of the westernmost outliers of the post-Roraima sandstones were deformed by the far-field effects of the Sunsas (Grenvillian) orogen at 1.33 Ga (Ar-Ar in muscovite). These results are based on U-Pb determinations of nine samples, Ar-Ar stepheating plateau age of one muscovite sample,and a complete review of many earlier Rb-Sr and K-Ar earlier dates. Keywords: Amazon craton, baddeleyite, diamond, Guyana Shield, Roraima, U-Pbgeochronology, zircon.